Characterization of Mongolian Gerbil Chromatoid Bodies and Their Correlation with Nucleolar Cycle During Spermatogenesis - Peruquetti, R. L. [UNESP]; Taboga, S. R. [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Wiley-Blackwell, 2010)
ContentsThe aims of the present study were to monitor the nucleolar cycle in Mongolian gerbil spermiogenesis, to verify the relationship between the nucleolar component and chromatoid body (CB) formation and to investigate the function of this cytoplasmic supramolecular structure in spermatogenic cells. Histological sections of adult seminiferous tubules were analysed cytochemically by light microscopy and ultrastructurally by transmission electron microscopy. The results reveal that in early spermatids, the CB was visualized in association with Golgi vesicles indicating that this structure may participate in the acrosome formation process as had been reported in other rodents. In late spermatids, the CB was observed near the axoneme region suggesting that this structure may support spermatozoon tail formation as happens in other species. Chromatoid body was joined with lipid droplets in this same cell type. This observation should be investigated to verify whether CB may be related to steroidal hormone metabolism. In conclusion, our data showed that there is disintegration of primary spermatocyte nucleoli at the beginning of prophase I and a fraction of this nucleolar material migrates to the cytoplasm, where a specific structure is formed, known as the 'chromatoid body', which apparently participates in some parts of the gerbil spermiogenesis process.